Can fundamental care be advanced using the science of care framework?. (11th August 2022) - Jeffs, Lianne; Merkley, Jane; Ronald, Kara; Newton, Gary; Yang, Lily; Gray, Carolyn Steele
Abstract: Aims: This manuscript aims to provide a description of an evidence‐informed Science of Care practice‐based research and innovation framework that may serve as a guiding framework to generate new discoveries and knowledge around fundamental care in a more integrated manner. Background: New ways of thinking about models of care and implementation strategies in transdisciplinary teams are required to accelerate inquiry and embed new knowledge and innovation into practice settings. A new way of thinking starts with an explicit articulation and commitment to the core business of the healthcare industry which is to provide quality fundamental care. Design: This discursive paper delineates an iteratively derived Science of Care research and innovation framework (Science of Care Framework) that draws from a targeted literature review. Method: The Science of Care Framework integrates caring science with safety and symptom sciences with implementation, improvement, innovation and team sciences. Each science dimension is described in terms of seminal and evolving evidence and theoretical explanations, focusing on how these disciplines can support fundamental care. Conclusions: The Science of Care Framework can serve as a catalyst to guide future efforts to propel new knowledge and discoveries around fundamental care and how best to implement it into clinical practice through a transdisciplinary lens. Impact on nursing science, practice, or disciplinary knowledge: The Science of Care Framework can accelerate nursing discipline‐specific knowledge generation alongside inter and transdisciplinary insights. The novel articulation of the Science of Care Framework can be used to guide further inquiries that are co‐designed, and led, by nurses into integrated models of care and innovations in clinical practice.